Pengaruh Penggunaan Pestisida Terhadap Kadar Cholinesterase Dan Kadar Hemoglobin Pada Petani Sawah Di Kelurahan Pammanu - Rismayanti Hasrum; Nasruddin Syam; Muhammad Ikhtiar (Window of Public Health Journal, 2025)
Based on data from the World Health Organization (WHO), every year there are 1-5 million cases of pesticide poisoning in farm workers with a death rate reaching 220. Pesticides are chemicals or mixtures of chemicals and other materials used to control or eliminate plant pests. Pesticides have the potential to contain toxins that are harmful to their users. One indicator of pesticide poisoning is to see the activity of Cholinesterase and hemoglobin levels in farmers' bodies. The purpose of this study was to see whether there was an effect of pesticide use on cholinesterase levels and hemoglobin levels in rice farmers. This type of research uses a quantitative research type with a cross-sectional study approach. The sampling technique used the purposive sampling method. The population in this study was 30 respondents. Data analysis was carried out univariately and bivariately using the chi-square test to determine the variables related to cholinesterase levels and hemoglobin levels. The results of the chi-square test analysis showed the p value of each variable including length of work p = 0.002, work period p = 0.483, spraying method p = 1,000, PPE p = 0.066 and spraying frequency. The hemoglobin levels of farmers were all normal. The conclusion of this study is that there is an influence between the length of work and the cholinesterase levels in rice farmers and there is no influence between the length of work, spraying method, spraying frequency and use of PPE on the cholinesterase levels in rice farmers. This study also found that there was no influence of pesticide use on hemoglobin levels in rice farmers because according to the examination using easy touch hb all farmers' hemoglobin levels were normal. These findings suggest that while the length of work may affect cholinesterase levels, other factors such as spraying method and frequency, and use of PPE, do not seem to have a significant impact. It is expected that farmers should check their cholinesterase levels at least once a year to see if there is an indication of poisoning in the body due to exposure to pesticides.